Clinical comparison between glucose and sucrose additions to a basic electrolyte mixture in the outpatient management of acute gastroenteritis in children. Issue 2 (February 1976) - Rahilly, P M; Shepherd, R; Challis, D; Walker-Smith, J A; Manly, J
Abstract : In a double-blind trial in 94 children attending outpatients the value of glucose or a sucrose addition to a basic electrolyte mixture for the management of acute gastroenteritis was compared. Of the children treated with added sucrose 10% failed to respond compared with 27% of those treated with added glucose. This difference was significant (P=0-05), but the time to recovery in those in the two groups who responded to treatment was not significantly different. Thus, despite theoretical advantages, there was no practical advantage in using glucose rather than sucrose. A 5% sucrose electrolyte solution with its relatively low osmolality, ready availability, and ease of preparation is recommended as the treatment of choice in the outpatient management of acute gastroenteritis in infancy.